2017
DOI: 10.4088/pcc.17m02179
|View full text |Cite
|
Sign up to set email alerts
|

Are Psychiatric Inpatients at Risk of Developing Wernicke’s Encephalopathy Being Identified and Adequately Treated?

Abstract: The findings suggest that Wernicke's encephalopathy is underdiagnosed and undertreated. Our study also highlights the need for clarifying diagnostic criteria, identifying the risk factors for thiamine deficiency, and improving awareness among physicians about diagnosis, prevention, and adequate treatment of Wernicke's encephalopathy in alcohol-dependent and non-alcohol-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently thiamine has also been found to be essential in the treatment of people with critical disease [4], strongly suggesting that energy is necessary for a successful outcome. It has been reported that in-patients being treated for psychiatric symptoms, are at risk for developing the serious symptoms of Wernicke Encephalopathy, well known to be due to thiamine deficiency [5]. A report from the Department of Infectious Diseases, Wenzhous Central Hospital, Zhejiang Province, China describes the symptoms of the patients with Coronavirus treated in that hospital.…”
Section: Does Selye's Work Apply To the Corona Virus?mentioning
confidence: 99%
“…Recently thiamine has also been found to be essential in the treatment of people with critical disease [4], strongly suggesting that energy is necessary for a successful outcome. It has been reported that in-patients being treated for psychiatric symptoms, are at risk for developing the serious symptoms of Wernicke Encephalopathy, well known to be due to thiamine deficiency [5]. A report from the Department of Infectious Diseases, Wenzhous Central Hospital, Zhejiang Province, China describes the symptoms of the patients with Coronavirus treated in that hospital.…”
Section: Does Selye's Work Apply To the Corona Virus?mentioning
confidence: 99%